Renewables : The Politics of a Global Energy Transition - Aklin, Michaël; Urpelainen, Johannes (Book collections on Project MUSE., 2018)
A comprehensive political analysis of the rapid growth in renewable wind and solar power, mapping an energy transition through theory, case studies, and policy.